2016
DOI: 10.1007/s11046-016-0068-6
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Dysbiosis and Yeast Isolation in Stool of Subjects with Autism Spectrum Disorders

Abstract: High frequency of gastrointestinal yeast presence in ASD subjects was shown through a simple cultural approach (Candida spp. in 57.5 % of ASDs and no controls); the identification of aggressive form (pseudo-hyphae presenting) of Candida spp. at light microscope means that adhesion to intestinal mucosa is facilitated. Dysbiosis appears sustained by lowered Lactobacillus spp. and decreased number of Clostridium spp. Absence of C. difficilis and its toxins in both ASDs and controls is also shown. Low-mild gut inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
142
3
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(181 citation statements)
references
References 57 publications
5
142
3
3
Order By: Relevance
“…We have previously reported that haemolytic bacteria are elevated in rats after exposure to heat stress (Ducray et al ). Additionally, others have reported that elevations in haemolytic bacteria and yeasts signify the occurrence of dysbiosis in weanling pigs (Poulsen et al ), patients with inflammatory bowel disease (Sokol et al ) and individuals with autism spectrum disorders (Iovene et al ). Bacteroides sp.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that haemolytic bacteria are elevated in rats after exposure to heat stress (Ducray et al ). Additionally, others have reported that elevations in haemolytic bacteria and yeasts signify the occurrence of dysbiosis in weanling pigs (Poulsen et al ), patients with inflammatory bowel disease (Sokol et al ) and individuals with autism spectrum disorders (Iovene et al ). Bacteroides sp.…”
Section: Discussionmentioning
confidence: 99%
“…The proliferation of Candida can be inhibited by IL-17, IL-22, which modulated by some species of Lactobacillus through tryptophan-derived aryl hydrocarbon receptor ligands (Zelante et al, 2013). Candida can releases ammonia and toxins that can induce autistic behaviors (Burrus, 2012; Iovene et al, 2017). The alterations of the bacterial microbiota in ASD individuals result in the expansion of Candida , which would worsen the dysbiosis and induce the abnormal behaviors.…”
Section: Relationship Between Asd and Gut Microbiotamentioning
confidence: 99%
“…Enhanced levels of gut permeability and associated alterations in gut microbiota are linked to the etiology and/or course of an array of medical conditions, including multiple sclerosis (13), Parkinson's disease (12), dementia (14), schizophrenia (15), bipolar disorder (16), the autistic spectrum (17) and depression (18). As noted above, the high rates of comorbid depression, often prior to symptom exacerbation, in these conditions suggests that gut-brain axis alterations may mediate some of their associations with such an array of medical presentations via raised levels of depression.…”
Section: The Gut-brain Axismentioning
confidence: 99%